An Analysis of the Impact of the Syrian Crisis on Turkey’s Politic-Military, Social and Economic Security - Sertif DEMİR; Muzaffer Ercan YILMAZ (Gazi Akademik Bakış)
This study analyzes how the ongoing Syrian Crisis has affected Turkey’s security. It starts with an overview of recent developments in the Middle East in general and in Syria specifically. It then examines the political, military, social, and economic effects of the Syrian Crisis for Turkey’s security. It concludes that the Syrian Crisis represents Turkey’s most challenging security problem since the end of the Second World War as it has had many profound impacts on the country.